Influence of Village Apparatus Competence And Clarity Of Budget Targets For Accountability Of Village Fund Management - Juwita, Rakhmini; Murti, Galuh Tresna (International Journal of Entrepreneurship and Business Management, 2023)
This study evaluated the accountability of village fund management in Ciparay Village, Bandung, West Java Indonesia. The precise goals were to determine how Village Apparatus Competence and Clarity of Budget Targets affected Acountability of Village Fund Management. The study was descriptive in nature, and the data collecting and analysis methods used were quantitative. A questionnaire was used to collect data from a sample of 56 responden. SPSS Version 25.0 and 5% significance level were used to analyze the data and produce both descriptive and inferential statistics. The study concluded. It was found that Village Apparatus Competence and Clarity of Budget Targets affected Acountability of Village Fund Management. It is hoped that this research can be used as an additional positive input reference for village officials, regional government and central government, to evaluate village fund allocation policies and systems to implement the principle of accountability in managing village funds. Apart from that, the community must also have awareness and concern so that they can participate in managing village funds.